The Impact of Asset Management on Company’s Operational Performance A Case of Horizon Construction Ltd (International Journal of Scientific Research and Management (IJSRM), 2021)
The efficiency of asset management for various reasons has been the focus for companies, Managers and investors doing construction businesses. The main objective of this research is to ascertain the effect of asset management practices on operational performance within Horizon Construction Ltd. To accomplish the main objective, three specific objectives were formulated. These include; to analyze the effect of standards compliance operational performance within Horizon Construction Ltd; to examine the effect of assets maintenance on operational performance within Horizon Construction Ltd and to assess the effect of budget allocation of funds on operational performance within Horizon Construction Ltd. The related theories including the resource based theory and the contingency theory, were used and analyzed. The population of the research are 200 participants and sample size is 66 respondents. The research tools for data collection are questionnaire, interview and documentation. The findings indicated that each unit of compliance with standards do not significantly influence each unit of operational performance in Horizon Construction Ltd. There is increase in each unit of operational performance when the unit of budget allocation of funds increases at 55.7% in Horizon Construction Ltd. There is an increase in each unit of operation performance when the unit of assets maintenance increases at 30.7% in Horizon Construction Ltd. Budget allocation of funds affects operational performance more than assets maintenance in the same perspective compliance with standards in asset management is on the third priority to affect operational performance in Horizon Construction Ltd. The results indicated that there is a positive auto-correlation between asset management (assets maintenance, compliance with standards, budget allocation of funds) and operational performance in Horizon Construction Ltd. This means that asset management can be associated with operational performance in Horizon Construction Ltd. There is a positive strong correlation between asset management and operational performance (R=0.993). The study concludes also that asset management (compliance with standards; assets maintenance and budget allocation of funds) had positive and significant effect cost efficiency in Horizon Construction Ltd. This means that as much as asset management is taught to the employees, there was an improvement on operational performance that will results in cost effective use of resources in Horizon Construction Ltd. This indicates that once employees are integrated in asset management system they will have accountability that will contribute to operational performance toward the achievement of the set goals within horizon construction Ltd.